ANALISIS PENERAPAN METODE SISOLMI DALAM PEMBELAJARAN INSTRUMEN BIOLA BERBASIS CARA BELAJAR SISWA AKTIF DI BAVISCH MUSIC SCHOOL - Wardoyo, Buchenita Naomi; Irawan, Ricky; Darmayuda, I Komang (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2024)
This research is motivated by the implementation of the Student Active Learning System (SAL/CBSA in Indonesia) in music education, specifically in violin instruction. The SAL system has been in existence since 1984 and is used in formal schools such as Elementary Schools, Junior High Schools, and Senior High Schools. In this case, the SAL system, which is typically applied in formal schools, is used in a music course setting, namely at Bavisch Music School. SAL itself can be applied in all branches of education, including formal, informal, and non-formal. However, the application of the SAL system to non-formal education, especially in violin instruction, differs slightly from its application in formal schools. Generally, SAL focuses on three aspects of education: cognitive, affective, and psychomotor. Its implementation in formal education differs from that in music courses, as the latter involves much more practical training, although the curriculum is also given significant attention.